The Age of Globalization and the Problem of Protecting the Environment (Texas Journal of Multidisciplinary Studies, 2023)
The current ecological crisis that worries humanity is expressed in the contradiction between the unlimited activity of man in relation to nature and the unlimited possibilities of the biosphere in providing human activity with resources. Many Western scientists emphasize that the elimination of the complex of global environmental problems is directly related to the growth of the planet's population, in other words, the "demographic explosion". This article focuses on environmental issues and environmental protection.